Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Tan, Runfa; Kang, Min Je; Qu, Li; Hwang, Sung Won; Hong, Seo Yeong; Jeong, Yoo Jae; Han, Hyun Soo; Kim, Dong Hoe; Lee, Sangwook; Cho, In Sun (Journal of Water Process Engineering, 2024)
Porosity control and facet engineering of electrocatalysts are critical for sustainable hydrogen production and wastewater upcycling into value-added chemicals. Herein, we report the sol-gel synthesis of a nanoporous faceted cupric oxide (nf-CuO) electrocatalyst film via a controlled polyesterification reaction. The formation mechanism of the unique nf-CuO morphology was analyzed and proposed. Notably, ligand additives such as ethylene glycol, citric acid, and polyethylene glycol function as morphology-controlling agents, and the polyesterification reaction between ligands can form covalent gel networks with trapped Cu ions. During thermal annealing, nucleation and nanoparticle growth along the covalent gel network enabled the formation of nanoporous and multifaceted CuO electrocatalysts on fluorine-doped SnO2 substrates, which was verified using ex-situ thermogravimetric/differential thermal analysis, Fourier transform infrared spectroscopy and transmission electron microscopy. The optimally synthesized nf-CuO exhibited high electrocatalytic activity in both photoelectrochemical hydrogen production and electrochemical nitrate reduction reactions. This enhanced performance was attributed to the nanoporosity-induced light-harvesting enhancement, enlarged surface area, and increased number of active sites. Our work emphasizes the importance of additive engineering to simultaneously control the porosity and facets of electrocatalysts and demonstrates its effectiveness in enhancing the electrocatalytic activity of diverse energy conversion devices.
Keywords: Cupric oxide; Electrocatalytic nitrate reduction; Facet; Nanoporous; Photoelectrochemical hydrogen production; Polyesterification